Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$$1 (N) + 2(N-1) + 3(N -2) + \cdots + i(N - i + 1) + \cdots + N (1) $$

I need to write it in simplest form?

here 1(N) means 1 multiply by N

share|improve this question
1  
Sorry, but does $N$ stand for a complex number? –  B. S. Nov 29 '12 at 10:05
    
Babak, $N$ must be a natural number; $i$ is intended as an index, not the square root of $-1$. So the sum is $\sum_{k=0}^{N-1} (1+k)(N-k)$. (Ah, now I see why you asked that. Grijesh, the tags you've chosen are completely inappropriate.) –  Rhys Nov 29 '12 at 10:12
    
What have you tried? –  Mark Bennet Nov 29 '12 at 10:13
1  
I am tiring to answer some other problem related to computer scince –  Grijesh Chauhan Nov 29 '12 at 10:17
add comment

3 Answers 3

up vote 5 down vote accepted

$$ \sum_{k=1}^Nk(N-k+1)=\sum_{k=1}^N kN-\sum_{k=1}^Nk^2+\sum_{k=1}^Nk=N\,\frac{N(N+1)}2-\frac{N(N+1)(2N+1)}6+\frac{N(N+1)}2=\frac{N(N+1)}2\left(N-\frac{2N+1}3+1\right)=\frac{N(N+1)(N+2)}6. $$

share|improve this answer
    
There is a typo. It should be N+2 in place of N+4. –  Gautam Shenoy Nov 29 '12 at 10:49
    
@Gautam Shenoy - thanks , Martin Argerami - thanks! –  Grijesh Chauhan Nov 29 '12 at 10:52
    
@draks 10/6 = 1 floor function –  Grijesh Chauhan Nov 29 '12 at 12:20
add comment

Your sum can be written as

$$\sum_{k=1}^Nk(N-k+1) = N\sum_{k=1}^{N}k - \sum_{k=1}^N{k^2} + \sum_{k=1}^N{k}$$

$$ = \frac{N(N+1)^2}{2} - \frac{N(N+1)(2N+1)}{6}$$

share|improve this answer
    
thank Gautam Shenoy ! –  Grijesh Chauhan Nov 29 '12 at 10:53
add comment

A more complex but fun alternative solution using Finite Calculus:

$$ \begin{align}  \sum_{x=1}^N x \left[(N+1)-x\right] & = \sum_{1}^{N+1} \left[ Nx - x(x-1)\right] \delta x = \sum_{1}^{N+1} \left( Nx^{(1)} - x^{(2)} \right) \delta x \\ & = \left[ \frac{N}{2}x^{(2)} - \frac{1}{3} x^{(3)} \right]_{1}^{N+1} = \left[ \frac{N}{2}x(x-1) - \frac{1}{3} x(x-1)(x-2) \right]_{1}^{N+1}\\ & = \left[ \frac{N(N+1)^2}{2} - 0 \right] - \left[ \frac{1}{3}(N+1)N(N-1) - 0 \right] \\ & = \frac{N(N+1)(N+2)}{6}. \end{align} $$

share|improve this answer
    
@ffrenz : Thanks frenz!! –  Grijesh Chauhan Nov 29 '12 at 12:41
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.